Transient gestational hypothyroxinemia accelerates and enhances ulcerative colitis-like disorder in the male offspring - Rivera, Juan Carlos; Opazo, Ma. Cecilia; Hernández-Armengol, Rosario; Álvarez, Oscar; Mendoza-León, María José; Caamaño, Esteban; Gatica, Sebastian; Bohmwald, Karen; Bueno, Susan M.; González, Pablo A.; Neunlist, Michel; Boudin, Helene; et al. (Frontiers in Endocrinology, 2024)
Gestational hypothyroxinemia (HTX) is a condition that occurs frequently at the beginning of pregnancy and it correlates with cognitive impairment, autism, and attentional deficit in the offspring. Evidence in animal models suggest that gestational HTX can increase the susceptibility for the offspring to develop strong inflammation in immune-mediated inflammatory diseases. Ulcerative colitis (UC) is a frequent inflammatory bowel disease which causes are unknown. Therefore, the intensity of ulcerative colitis-like disorder (UCLD) and cellular and molecular factors that participate as proinflammatory or anti-inflammatory were analyzed in the offspring gestated in HTX (HTX-offspring) and compared to the offspring gestated in euthyroidism (Control-offspring).Gestational HTX was induced by administration of methylimidazole in the drinking water to pregnant mice during E10-E15. The HTX-offspring were induced with UCLD by acute administration of dextran sodium sulphate (DSS). The score of UCLD symptomatology was registered every day and colon histopathology, immune cells and molecular factors involved in the inflammatory or anti-inflammatory response were analyzed at day six of DSS treatment. The HTX-offspring displayed earlier UCLD pathological symptoms compared to Control-offspring. After six days of DSS treatment the HTX-offspring almost doubled the score of Controloffspring. The histopathological analyses of colon samples showed signs of inflammation at distal and medial colon for both HTX-offspring and Control-offspring. However, significantly more inflammatory features were detected in the proximal colon of the HTX-offspring induced with UCLD compared to Control-offspring induced with UCLD. A significant reduced mRNA content encoding for protective molecules like glutamatecysteine ligase catalytic subunit (GCLC) and Mucin-2 (MUC-2) were found at the colon of HTX-offspring as compared to Control-offspring. Higher percentages of Th17 lymphocytes were detected at the colon tissues of HTX-offspring induced or not with UCLD as compared to Control-offspring. Gestational HTX accelerates the onset and increases the intensity of UCLD in the offspring. The low expression of MUC-2 and GCLC together with high levels of TH17 at the colon tissue suggest that the HTX-offspring has molecular and cellular features that favor inflammation and tissue damage. These results are important evidence to awareness about the impact of gestational HTX as a risk factor for UCLD development in their offspring.